Willingness and readiness to use digital technologies in midwifery practice among midwives at tertiary health facilities in Uganda. A qualitative and phenomenological Study. : Training and Education - Asaba , Marion; Omolara Tella; Ijeoma Ihekwaba; Adedayo Omolara Tella (Student's Journal of Health Research Africa, 2022)
Background: Digital technologies being used to promote maternal health and support service providers have increased dramatically during the last 20 years. The internet, mobile technologies such as mobile software programs or apps, wearables, Texting, social networking, telecare, and remote monitoring equipment are all examples of digital forms of support. Digital technologies for health have emerged as a prominent field of practice for utilizing both standard and novel kinds of applications of information and communication technology to solve upcoming health complications, particularly in the field of midwifery. The study objective was to explore the willingness and readiness to use digital technologies in midwifery practice among midwives at tertiary health facilities in the Buikwe district in Uganda. Methodology: Using the qualitative and phenomenological design, a purposive sampling technique was employed to select 15 interviewees from Kawolo and St. Charles Lwanga Hospitals. Data collection was by use of an interview guide, and data analysis involved Thematic content analysis. The results showed nearly all of the midwives were ready to use digital technology. Results: Altogether, six thematic areas emerged as considerations when getting ready to use digital technologies: improved patient care, communication, training and education, information sharing, age, and attitudes toward digital technology. The drawbacks included; high costs of devices and data, attitude, and unavailability of digital technologies. Conclusion: Majority of the midwives are willing and ready to use digital technologies. Therefore, they need to be encouraged and facilitated accordingly since technology integration into midwifery practice can improve the overall health of mothers and their babies. Recommendations: This study recommends that; The government should provide more digital technologies in hospitals, subsidize mobile data costs and the market price of smartphones, Internet access is promised in major departments, and free internet access for research purposes will be provided.